2023
DOI: 10.2196/49918
|View full text |Cite
|
Sign up to set email alerts
|

The DrinksRation Smartphone App for Modifying Alcohol Use Behaviors in UK Military Service Personnel at Risk of Alcohol-Related Harm: Protocol for a Randomized Controlled Trial

Abstract: Background Consumption of alcohol is synonymous with military populations, and studies have shown that serving personnel drink more than age- and sex-matched civilian populations. While ingrained in the military culture, excessive alcohol use is associated with increased rates of disciplinary issues, sickness absence, and loss of productivity, as well as contributing to a burden of acute and chronic health problems. Alcohol brief interventions can reduce alcohol use in civilian populations, but the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The app is freely available on the Apple App Store and Google Play Store. The app has received support and endorsement from Combat Stress and is currently being trialed among serving personnel [ 15 ]. DrinksRation is supported by a robust evidence base, including a randomized controlled trial (RCT) that demonstrated that the app is efficacious in reducing alcohol consumption [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The app is freely available on the Apple App Store and Google Play Store. The app has received support and endorsement from Combat Stress and is currently being trialed among serving personnel [ 15 ]. DrinksRation is supported by a robust evidence base, including a randomized controlled trial (RCT) that demonstrated that the app is efficacious in reducing alcohol consumption [ 12 ].…”
Section: Introductionmentioning
confidence: 99%